Impaired inflammatory resolution with severe SARS-CoV-2 infection in leptin knock out obese hamster - Ren-Di Jiang; Yun-Zhe Luo; Hao-Feng Lin; Xiao-Shuang Zheng; Wen-Tao Zeng; Mei-Qin Liu; Hao-Hao Deng; Qi Wang; Ya-Na Lai; Ying Chen; Zi-Shuo Guo; Ya Zeng; et al. (iScience)
Summary: Comorbidities, such as obesity, increase the risk of severe COVID-19. However, the mechanisms underlying severe illnesses in individuals with obesity are poorly understood. Here, we used gene-edited leptin knock out (Leptin−/−) obese hamsters to establish a severe infection model. This model exhibits robust viral replication, severe lung lesions, pronounced clinical symptoms, and fatal infection, mirroring severe COVID-19 in patients with obesity. Using single-cell transcriptomics on lung tissues pre- and post-infection, we found that monocyte-derived alveolar macrophages (MD-AM) play a key role in lung hyper-inflammation, including two unique MD-AM cell fate branches specific to Leptin−/− hamsters. Notably, reduced Trem2-dependent efferocytosis pathways in Leptin−/− hamsters indicated weakened inflammation resolution, consistent with the scRNA-seq data from patients with obesity. In summary, our study highlights the obesity-associated mechanisms underlying severe SARS-CoV-2 infections and establishes a reliable preclinical animal model for developing obesity-specific therapeutics for critical COVID-19.